2015
DOI: 10.1016/j.jlp.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviour of direct spring loaded pressure relief valves in gas service: II reduced order modelling

Abstract: A previous study of gas-service direct-spring pressure relief valves connected to a tank via a straight pipe is continued by deriving a reduced-order model for predicting oscillatory instabilities such as valve flutter and chatter. The reduction process uses collocation to take into account a finite number N of acoustic pressure waves within the pipe, resulting in a set of 2N + 3 ordinary differential equations. Following a novel non-dimensionalization, it is shown analytically that the model can exhibit, at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 8 publications
3
35
0
Order By: Relevance
“…This paper continues the previous work by the present authors in Hős et al (2014Hős et al ( , 2015 on practical considerations of mechanisms of instability in direct spring operated pressure relief valves (PRVs). Here we specifically consider valves in liquid, rather than gas, service.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…This paper continues the previous work by the present authors in Hős et al (2014Hős et al ( , 2015 on practical considerations of mechanisms of instability in direct spring operated pressure relief valves (PRVs). Here we specifically consider valves in liquid, rather than gas, service.…”
Section: Introductionsupporting
confidence: 76%
“…Instead, in Hős et al (2015) we found an accurate stability criterion which we tested against experimental results for three different commercially available gas service PRVs. The key is to recognize that the fundamental instability causing valve flutter is a flow-induced Hopf bifurcation caused by an interplay between the valve natural dynamics and the fundamental quarterwave acoustic vibration mode in the pipe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a very common method to examine nonlinear systems in general, for details see e.g. [46][47][48][49]. The IVP solver was a 4th order Runge-Kutta scheme with 5th order embedded error estimation.…”
Section: Numerical Toolsmentioning
confidence: 99%
“…The corresponding industrial standard [1] and the literature [9] usually discusses stability as a function the driving mass flow rate and pipe length. This map can be seen in Figure 3(b).…”
Section: Resultsmentioning
confidence: 99%